Assessment of the incidence of neonatal sepsis, its risk factors, antimicrobials use and clinical outcomes in Bishoftu General Hospital, neonatal intensive care unit, Debrezeit-Ethiopia - Woldu, Minyahil Alebachew; Guta, Molla Belay; Lenjisa, Jimma Likisa; Tegegne, Gobezie Temesgen; Tesafye, Gurmu; Dinsa, Hunduma (International Journal of Contemporary Pediatrics, 2017)
Background: The incidence of neonatal sepsis (NS) varies from 6 to 9 cases per 1000 live births, but is higher among low-birth-weight neonates. Therefore, the purpose of this study was to examine the risk factors, antimicrobial use pattern and clinical outcomes of NS at Bishoftu General Hospital, neonatal intensive care unit, Debrezeit-Ethiopia. Methods: A prospective cross-sectional study was conducted using pretested and validated checklists. Results: Among the total 306 neonates (0-28 days of age) recruited, 249 (81.4%) were age ≤7 days, 169 (55.23%) were male, 251 (82%) were attended antenatal care, 136 (44.44%) were low in birth weight (≤2.5 kg) and 155 (50.7%) had total of white blood cell count ≥12000/mm3. 221 (72.2%) of the neonates diagnosed as sepsis received antibiotics while 74 (24.2%) received antibiotics for other diagnosis. The most frequently prescribed antibiotic was the combination of ‘ampicillin + gentamicin’ prescription 67 (21.9%) followed by the single antibiotic prescriptions of benzyl penicillin 33 (10.8%) and cloxacillin 8 (2.6%). A significant number of neonates (p = 0.000) with 95% confidence interval of (1.934-8.967) were born in health center and developed sepsis. This value is 4.2 times higher when compared with the neonates born in the home. A significant number of neonates using instrument in hospitals were also developed sepsis (p = 0.26). The risk of acquiring sepsis in neonates born using instrument was almost 6.2 times more common than children born vaginal in the natural way. A significant number of neonates born from mothers’ with urinary tract infections (UTI) developed sepsis (p = 0.02) and this figure was almost 2.9 times higher compared to neonates born from mothers’ with no UTI diagnosis. Conclusions: In the present study, the most common risk factors were identified and place of delivery, mode of delivery and mother with UTI during delivery were the most common risk factors for the incidence of NS.